CATEGORY OF BEING: HISTORY AND MODERN AGE - A. A. Mazhitov (Наука и техника)
The paper investigates a category of being in its historical development. The revealed relation of being with worldview and self-understanding underlines the importance of adequate being understanding for preservation of really human being existence.